Greener synthesis of nanostructured iron oxide for medical and sustainable agro-environmental benefits - Poh Yan, Leong; Gopinath, Subash C. B.; Subramaniam, Sreeramanan; Chen, Yeng; Velusamy, Palaniyandi; Chinni, Suresh V.; Gobinath, Ramachawolran; Lebaka, Veeranjaneya Reddy (Frontiers in Chemistry, 2022)
Nanoscale iron oxide-based nanostructures are among the most apparent metallic nanostructures, having great potential and attracting substantial interest due to their unique superparamagnetic properties. The green production of nanostructures has received abundant attention and been actively explored recently because of their various beneficial applications and properties across different fields. The biosynthesis of the nanostructure using green technology by the manipulation of a wide variety of plant materials has been the focus because it is biocompatible, non-toxic, and does not include any harmful substances. Biological methods using agro-wastes under green synthesis have been found to be simple, environmentally friendly, and cost-effective in generating iron oxide-based nanostructures instead of physical and chemical methods. Polysaccharides and biomolecules in agro-wastes could be utilized as stabilizers and reducing agents for the green production of nanostructured iron oxide towards a wide range of benefits. This review discusses the green production of iron oxide-based nanostructures through a simple and eco-friendly method and its potential applications in medical and sustainable agro-environments. This overview provides different ways to expand the usage of iron oxide nanomaterials in different sectors. Further, provided the options to select an appropriate plant towards the specific applications in agriculture and other sectors with the recommended future directions.